2007
DOI: 10.1111/j.1462-2920.2007.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas community structure and antagonistic potential in the rhizosphere: insights gained by combining phylogenetic and functional gene‐based analyses

Abstract: The Pseudomonas community structure and antagonistic potential in the rhizospheres of strawberry and oilseed rape (host plants of the fungal phytopathogen Verticillium dahliae) were assessed. The use of a new PCR-DGGE system, designed to target Pseudomonas-specific gacA gene fragments in environmental DNA, circumvented common biases of 16S rRNA gene-based DGGE analyses and proved to be a reliable tool to unravel the diversity of uncultured Pseudomonas in bulk and rhizosphere soils. Pseudomonas-specific gacA fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 62 publications
6
74
1
5
Order By: Relevance
“…This is in line with previous reports that demonstrated the influence of plant species on global communities (Westover et al, 1997;Marschner et al, 2004Marschner et al, , 2005Phillips et al, 2006) as well as on specific phylogenetic or functional groups of rhizosphere bacteria (Costa et al, 2006(Costa et al, , 2007Patra et al, 2006). Surprisingly, there was no effect of plant species in rhizosphere soil communities, in contrast to what was observed by Jossi et al (2006), where the effect of plant species was also clearly visible in the soil communities.…”
Section: Impact Of Plant Species On Bacterial Community Structuresupporting
confidence: 92%
“…This is in line with previous reports that demonstrated the influence of plant species on global communities (Westover et al, 1997;Marschner et al, 2004Marschner et al, , 2005Phillips et al, 2006) as well as on specific phylogenetic or functional groups of rhizosphere bacteria (Costa et al, 2006(Costa et al, , 2007Patra et al, 2006). Surprisingly, there was no effect of plant species in rhizosphere soil communities, in contrast to what was observed by Jossi et al (2006), where the effect of plant species was also clearly visible in the soil communities.…”
Section: Impact Of Plant Species On Bacterial Community Structuresupporting
confidence: 92%
“…In addition, B. dendrobatidis zoospores exhibit chemotaxis away from several of these compounds (79). Therefore, dominant bacteria that produce secondary metabolites with antifungal properties may also play important roles in host defense, as demonstrated previously in a plant rhizosphere microbial community (80). Specifically, Costa et al (80) demonstrated that the most dominant members exhibited antagonistic properties against a plant fungal pathogen.…”
Section: Discussionmentioning
confidence: 83%
“…To test the hypothesis that the effect of genetic modification of the GM lines on rhizosphere communities was less pronounced than the effect of genotype differences among cultivars, the similarities of the DGGE fingerprints of all plant genotypes to that of 'Baltica' were compared. Analysis of the median similarities of all bacterial fingerprints for samples obtained from both Roggenstein (in 2005 and2007) and Oberviehhausen (in 2006) revealed that the GM lines were, on average, more similar to the parent 'Baltica' than all other cultivars were (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%